2016
DOI: 10.5194/acp-16-15359-2016
|View full text |Cite
|
Sign up to set email alerts
|

Variability of winter and summer surface ozone in Mexico City on the intraseasonal timescale

Abstract: Abstract. Surface ozone concentrations in Mexico City frequently exceed the Mexican standard and have proven difficult to forecast due to changes in meteorological conditions at its tropical location. The Madden-Julian Oscillation (MJO) is largely responsible for intraseasonal variability in the tropics. Circulation patterns in the lower and upper troposphere and precipitation are associated with the oscillation as it progresses eastward around the planet. It is typically described by phases (labeled 1 through… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Larger-scale meteorology influences surface O 3 concentrations. Barret and Raga [69] observed that the intraseasonal variability of surface O 3 , in both summer and winter, is driven by the variability in the cloud cover due to the upper-troposphere circulation modulated by the Madden-Julian oscillations (MJO). Also, stratospheric O 3 intrusions into the boundary layer were identified by Barret et al [70] during a stratosphere-troposphere exchange event linked to changes in the subtropical jet stream.…”
Section: Meteorologymentioning
confidence: 99%
“…Larger-scale meteorology influences surface O 3 concentrations. Barret and Raga [69] observed that the intraseasonal variability of surface O 3 , in both summer and winter, is driven by the variability in the cloud cover due to the upper-troposphere circulation modulated by the Madden-Julian oscillations (MJO). Also, stratospheric O 3 intrusions into the boundary layer were identified by Barret et al [70] during a stratosphere-troposphere exchange event linked to changes in the subtropical jet stream.…”
Section: Meteorologymentioning
confidence: 99%
“…The zonal jet extension occurred possibly due to the mechanism proposed by Weickmann and Berry (, ): a very active Madden‐Julian Oscillation event traversed the Maritime Continent and Western Pacific in February 2016 (leading to a strengthening of the subtropical jet in early March), which then transitioned into the Western Hemisphere and Indian Ocean the first week of March 2016 (leading to an increase in jet waviness after 07 March 2016). This physical mechanism is supported by Barrett and Raga (), who noted that high surface O 3 concentrations in Mexico City tend to be favored on days when the Real‐time Multivariate Madden‐Julian Oscillation (Wheeler & Hendon, ) index is in phases 2 and 3, which it was from 09 to 13 March 2016. Second, the subtropical jet became baroclinically unstable and wavy. Third, one of those waves, a pronounced anticyclonic ridge along 150°W, underwent anticyclonic wave breaking between 35 and 45°N. Fourth, that wave breaking led to the development of an anomalously deep and equatorward cutoff low between 15 and 25°N. Fifth, the deep low brought O 3 ‐rich stratospheric air well into the troposphere via a pronounced STE event seen in vertical profiles of both PV and O 3 concentration in the air column above Mexico City. This O 3 ‐rich air remained in the air column on 11 and 12 March 2016, likely mixing to the surface on those days and re‐entraining into the ABL due to basin‐wide mesoscale circulations on 13 March 2016. Sixth, subsidence behind the low both suppressed the development of convective clouds and led to the formation of strong thermal inversions near 650 hPa.…”
Section: Conclusion and Discussionmentioning
confidence: 64%
“…The zonal jet extension occurred possibly due to the mechanism proposed by Berry (2007, 2009): a very active Madden-Julian Oscillation event traversed the Maritime Continent and Western Pacific in February 2016 (leading to a strengthening of the subtropical jet in early March), which then transitioned into the Western Hemisphere and Indian Ocean the first week of March 2016 (leading to an increase in jet waviness after 07 March 2016). This physical mechanism is supported by Barrett and Raga (2016), who noted that high surface O 3 concentrations in Mexico City tend to be favored on days when the Real-time Multivariate Madden-Julian Oscillation (Wheeler & Hendon, 2004) index is in phases 2 and 3, which it was from 09 to 13 March 2016. 2.…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 72%
“…Any comparison study has to consider these fast changing O 3 concentrations and we only compare data that are measured within the same hour. A discussion on O 3 boundary layer variability of Mexico City on time scales beyond the diurnal time scale is given in Barrett and Raga (2016).…”
Section: In-situ Monitoring Of Air Pollution In Mexico Citymentioning
confidence: 99%